(untitled) (SIRJANĀ – A Journal Of Arts and Art Education, 2024)
Contemporary Nepali artist Sharada Man Shrestha uses scraps, junks, leftovers and found objects in his sculptures, paintings and installations. He transforms junks and leftovers into beautiful and fine aesthetic objects. The scraps and junks in mess distract the pedestrians but his artworks provide aesthetic pleasure to the viewers. Use of such materials in art contributes to manage the junks and scraps, recycle the used things, save the resources, reduce the environmental pollution, create cultural identity of the artist and the nation and earn livelihood for the artist. Shrestha has created both figurative and abstract artworks using scraps like used bottles, tires, pipes, grinding wheels and thrown away motorcycle parts. He has created high relief, low relief and freestanding sculptures. Due to the presence of physical material in the works rather than the creation of illusion through colors and light, the creative works provide a sense of connectedness to the earth. This article explores the principles behind the use of junks and interprets the artworks of Sharada Man Shrestha and shows how junks get transformed into the aesthetic objects. Since the thesis statement is supported through the interpretation of artworks, it is qualitative research.